The Pavilion of Israel (Benjamin New Co., Ltd.)
The Pavilion of Israel is situated on Ile Notre-Dame. The architecture and exhibits, jointly planned and imaginatively conceived, using the latest artistic devices in display, take the visitor through Jewish history from early times to the lively vibrance of present day Israel society.